Telemedicine in Pediatric Cardiology: Current Applications, Clinical Impact, and Future Perspectives - Luisa M. Rizzo; Matilde Petz; Federico Carlini; Susanna Esposito (Journal of Personalized Medicine, 2026)
Telemedicine is increasingly transforming pediatric cardiology by expanding access to specialized care, supporting early diagnosis, and improving longitudinal monitoring of children with cardiovascular disease. This narrative review summarizes current applications of digital health in pediatric cardiology, with emphasis on congenital heart disease, pediatric hypertension, and arrhythmia management. Tele-echocardiography represents one of the most established telehealth tools, enabling remote interpretation of fetal, neonatal, and pediatric echocardiographic images and improving referral appropriateness, particularly in peripheral or resource-limited settings. In infants with complex congenital heart disease, especially those with single-ventricle physiology during the interstage period, home monitoring programs using mobile applications, pulse oximeters, digital scales, and structured caregiver reporting may facilitate early recognition of clinical deterioration and reduce avoidable transfers. In non-congenital cardiovascular disease, home blood pressure monitoring can improve diagnostic accuracy by reducing white-coat effects and supporting repeated measurements in real-life settings. Smartphone-enabled electrocardiographic devices and wearable technologies may enhance detection of intermittent arrhythmias and strengthen outpatient management. Despite these advantages, challenges remain, including data fragmentation, limited pediatric validation of consumer devices, interoperability issues, privacy concerns, and socioeconomic disparities in technology access. Properly integrated telemedicine may promote more timely, equitable, and patient-centered pediatric cardiovascular care.